Selection, hybridization, and the evolution of morphology in the Lake Malaŵi endemic cichlids of the genus Labeotropheus. Issue 1 (December 2018) - Pauers, Michael; Fox, Kelsey; Hall, Robert; Patel, Kesha
Abstract The cichlid fishes of Lake Malaŵi are the paramount example of adaptive radiation in vertebrates. Evidence of their astounding diversity is perhaps most visible in their adaptations for obtaining food; the genusLabeotropheus, due to their prominent snouts, are an interesting example of an extreme adaptation for feeding. Two different body types are found in this genus: a deep-bodied form (e.g., L .fuelleborni ) found most often in turbulent shallow water; and a slender bodied form (e.g., L .trewavasae ) found in structurally-complex deep water habitats. Here we test the hypothesis thatL .trewavasae should suffer a loss in fitness, measured as growth rate, if raised in turbulence; additionally, we examined growth and morphology ofL .fuelleborni andL .fuelleborni xL .trewavasae hybrids under these conditions. We did find the predicted loss of fitness in turbulent-raisedL .trewavasae, but found no loss of fitness forL .fuelleborni in either condition; hybrids, due to an unusual morphology, performed better in turbulent as opposed to control conditions. Fitness in turbulent conditions was dependent upon morphology, with deeper bodies and upturned neurocrania allowing a greater growth rate under these conditions. Directional selection on morphology was crucial in the evolution of morphology in theLabeotropheus .